PEMANFAATAN MEDIA SOSIAL INSTAGRAM DALAM PENYEBARAN INFORMASI PELATIHAN TENAGA KERJA BERBASIS KOMPETENSI DI KELURAHAN GUNUNG SETELENG MELALUI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN PENAJAM PASER UTARA - Yaksi Belaning Pratiwi Kuncoro; Andi Vita Sukmarini; Fitriani Fitriani (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the use of Instagram social media in disseminating competency-based workforce training information as well as supporting and inhibiting factors of Instagram social media in implementing competency-based workforce training. The results of this study indicate that the use of Instagram social media in disseminating competency-based workforce training information in Gunung Seteleng Village through the Manpower and Transmigration Office of North Penajam Paser Regency has been maximized because Instagram is the fastest growing social media and almost everyone knows and uses Instagram. Supporting factors include complete and interesting features, user interest and enthusiasm, ease of interaction and communication, broad potential for use, popular media platforms, Instagram as a free application that can be downloaded by anyone, ease of use of features provided by Instagram is easy and fast in disseminating information, reaching a wide target, which has the meaning of Instagram social media utilization of Instagram social media as a promotional media that has a very large influence on the reach of information, the existence of information in the category of government agencies, increasing the number of competency-based training registrations, and the availability of budgets and operational support facilities for Instagram social media. Meanwhile, inhibiting factors include privacy and security issues, trust and fraud issues, potential negative social impacts, competition for user attention because Instagram is a platform dense with various brands, determining ideas and concepts, having to monitor comments from people who want to take part in workforce training, dividing time, and lack of human resources.